Advancing cancer care through digital access in the USA: a state-of-the-art review of patient portals in oncology - Liz Salmi; Jessica Ancker; Lisa Diamond; Uday Suresh; Trent Rosenbloom; Bryan Steitz (BMJ Oncology)
Patient portal use among patients with cancer has increased significantly in recent years. This state-of-the-art review seeks to address and analyse literature involving patient portal use by patients with cancer and their care partners. In this review, we queried articles from PubMed published between January 2018 and April 2024 that describe recent trends and the current presence of portals in cancer care for patients, proxy users and/or care partners. We searched for articles addressing three overarching themes: (1) trends and disparities in portal adoption and use among patients with cancer, (2) use of specific portal components and functions in cancer care and (3) associations between portal use and cancer-related outcomes. Our search identified 278 unique studies, of which 82 were relevant empiric studies that met inclusion criteria and were included in this review. These papers aligned with 12 subthemes, including disparities in patient portal access, growing use of telemedicine via patient portal and patient access to immediately available to electronic health information. Our findings indicate that patient portals play an increasingly important role in helping patients manage their cancer care, despite few disparities that contribute to inequitable use. However, despite consistent growth in use over recent years, there are many areas for improvement in how portals support patients with cancer and a demand for functionality to continually evolve with patient needs.